Agriculture and the environment: Two often opposing forces which must work together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Throughout Africa the population is ever growing. Because of this the age-old shifting methods of farming are under pressure to give way to continuous and intensive cultivation, and the environment is suffering more and more as a consequence. But...